2020
DOI: 10.1007/s10346-020-01421-7
|View full text |Cite
|
Sign up to set email alerts
|

Structurally controlled rock slope deformation in northern Norway

Abstract: Gravitational forcing of oversteepened rock mass leads to progressive failure, including rupture, creeping, sliding and eventual avalanching of the unstable mass. As the point of rupture initiation typically follows pre-existing structural discontinuities within the rock mass, understanding the structural setting of slopes is necessary for an accurate characterisation of the hazards and estimation of the risk to life and infrastructure. Northern Norway is an alpine region with a high frequency of large rock sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 71 publications
(132 reference statements)
1
20
0
Order By: Relevance
“…Large disruptive landslides may represent the ultimate stage of the MRC process that can culminate in paroxysmal events (like rock avalanches); nevertheless, these ultimate events are anticipated by gravity-driven deformations which represent the strain effect of the rock mass viscous rheology. When these deformations develop into abrupt and generalized slope failures, it is caused by an increasing strain rate over time [10]. In particular, threshold conditions can be reached when the stationary creep stage evolves into an accelerating creep stage [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Large disruptive landslides may represent the ultimate stage of the MRC process that can culminate in paroxysmal events (like rock avalanches); nevertheless, these ultimate events are anticipated by gravity-driven deformations which represent the strain effect of the rock mass viscous rheology. When these deformations develop into abrupt and generalized slope failures, it is caused by an increasing strain rate over time [10]. In particular, threshold conditions can be reached when the stationary creep stage evolves into an accelerating creep stage [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term strength is involved to test the stability of surrounding isotropic rock in a long duration of time because of the consideration of time effect, such as rock creep or the saturation by surface or underground water. However, rare analytical solutions regarding long-term strength of discontinuities have been reported, even though the impact of time on discontinuities' strength has been commonly observed [40,41]. Thus, the time effect is not involved in the proposed model for the slip failure (Equations ( 11), (12), and (13a)-(13d)), and this leads to observed orientation range where surface subsidence extension that takes place is larger than the predicted.…”
Section: Implications From the Proposed Model And Illustrativementioning
confidence: 98%
“…The control factors of DSGSDs are numerous and mainly related to the characteristics of the relief and to the inherited and pre-existing structures [17,25]. Among them, of particular importance are tectonic structures such as folds and faults [17,19,26,30,35,39,42,47,48,76,[78][79][80] and bedding planes or schistosity [21,35,48,51,81]. These structures act as preferential weakness planes (or zones) and affect the geomechanical and rheological properties of rock masses [18,21,[49][50][51].…”
Section: Control Factorsmentioning
confidence: 99%
“…Some authors identified the absence of continuous sliding surface or basal shear zone as a typical feature of DSGSDs, thus considering them as discriminating elements with respect to "conventional" landslides [14]. Notwithstanding, these features have been recognized or inferred in many DSGSDs [15,17,18,[31][32][33][34][35] and so they have lost their value as discriminating element.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation